Keagresifan Beberapa Isolat Fusarium oxysporum f. sp. zingiberi Asal Temanggung dan Boyolali Setelah Penyimpanan dalam Tanah Steril - Henky Setyawan Norandika Wahyu; Loekas Soesanto; Kustantinah Kustantinah (Jurnal Fitopatologi Indonesia, 2012)
Preservation of fungi isolates is needed for further research but usually the preservation treatment is only concerned on life span and growth of the fungi. This research aimed at knowing life span and aggressivity of Fusarium oxysporum f. sp. zingiberi isolates from ginger cv. Gajah after preserving for three years in sterile soil. Completely Randomized Design and Randomized Block Design were used for in vitro and in planta test, respectively, with 10 isolates of F. oxysporum f. sp. zingiberi from Temanggung, 8 isolates of F. oxysporum f. sp. zingiberi from Boyolali, and 1 control, each repeated three times. Variables observed were incubation period, infected area, disease intensity, rhizome wet weight, number of leaves, and crop height. Result of the research showed that all isolates of F. oxysporum f. sp. zingiberi could still grew well. Based on origin of the isolates, the highest aggressivity on ginger rhizome was TKO3 from Temanggung and BAO6 from Boyolali with infected area of 67.67 mm2 and 56.67 mm2, respectively. On ginger crop, the highest aggressivity was BAO1 from Boyolali and TPO2 from Temanggung with disease intensity of 68.09% and 38.13%, respectively. All isolates of F. oxysporum f. sp. zingiberi did not cause significantly different effect on incubation period, disease intensity, crop height, leaves total, and rhizome wet weight but they caused significantly different effect on infected area.   Key word: aggressivity, Fusarium oxysporum, ginger, preservation, steril soil